Innovating Development Finance : From Financing Sources to Financial Solutions - Girishankar, Navin (2012)
As early as 2000, development partners embarked on a decade-long search for "innovative" or alternative sources of Official Development Assistance to help finance achievement of the Millennium Development Goals. For their part, developing countries have sought not only more financial flows but better financial solutions, for example, through partnerships that mobilize private finance for public service delivery, risk mitigation efforts that promote private entry in the productive sectors, and support for carbon trading. This paper offers a framework to organize and understand this heterogeneous mix of innovations in fund-raising and financial solutions for development. It also provides, for the first time, a stocktaking of actual innovations that make up the international landscape and highlights the World Bank Group s role to date. The stocktaking shows that innovative finance mechanisms have played a more significant role in supporting financial solutions on the ground than in identifying and exploiting "alternative sources of ODA." Innovative fund-raising therefore should be viewed as a complement to - rather than a substitute for - traditional efforts to mobilize official flows, in particular concessional flows. Going forward, innovations need to be tested and evaluated to determine value-added.